2009
DOI: 10.2146/ajhp080711
|View full text |Cite
|
Sign up to set email alerts
|

Treatment persistence in and cost of therapy for patients with chronic hepatitis C: Peginterferon alfa-2a plus ribavirin versus peginterferon alfa-2b plus ribavirin

Abstract: Analysis of information from a health care claims database suggests that treating CHC with peginterferon alfa-2a plus ribavirin may improve treatment persistence and help reduce the health care costs imposed by CHC compared with treatment with peginterferon alfa-2b plus ribavirin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…A few studies reported similar or better levels of persistence than those found in our study; however, all of these were much smaller and shorter and did not include follow-up within the recent era of greater DMT choice [ 10 , 18 , 29 ]. The persistence rates for GA and IFN-β reported here are also substantially higher than for injectable treatments for Type-II diabetes, schizophrenia, and hepatitis C [ 30 38 ]. Therefore, in comparison with most studies of injectable therapies in MS and other chronic diseases, patients with MS in our clinic have been outstanding in their ability to remain on injectable therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies reported similar or better levels of persistence than those found in our study; however, all of these were much smaller and shorter and did not include follow-up within the recent era of greater DMT choice [ 10 , 18 , 29 ]. The persistence rates for GA and IFN-β reported here are also substantially higher than for injectable treatments for Type-II diabetes, schizophrenia, and hepatitis C [ 30 38 ]. Therefore, in comparison with most studies of injectable therapies in MS and other chronic diseases, patients with MS in our clinic have been outstanding in their ability to remain on injectable therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Noncompliance with treatment and medical advice may cause accelerated disease, increased outpatient visits, more admissions to hospital, and impaired ability to predict the effectiveness of treatment 6. In addition, increased morbidity and mortality due to noncompliance may increase health care costs 7–10…”
Section: Introductionmentioning
confidence: 99%